High maternal mortality rate associated with advanced maternal age in Japan - Hiroaki Tanaka; Junichi Hasegawa; Shinji Katsuragi; Kayo Tanaka; Tatsuya Arakaki; Masamitsu Nakamura; Eijiro Hayata; Masahiko Nakata; Takeshi Murakoshi; Akihiko Sekizawa; Isamu Ishiwata; Tomoaki Ikeda (Scientific Reports, 2023)
Abstract This study aimed to clarify the relationship between maternal mortality and advanced maternal age in Japan and to provide useful information for future perinatal management. Maternal death rates by age group were investigated for all maternal deaths in Japan for an 11-year period, from 2010 to 2021. Maternal deaths among those aged ≥ 40 years were examined in detail to determine the cause, and the number of deaths by cause was calculated. The causes of onset of the most common causes of death were also investigated. The maternal mortality rates were 0.8 (95% confidence interval [CI] 0.3–4.7) for < 20 years, 2.6 (95% CI 1.7–3.8) for 20–24 years, 2.9 (95% CI 2.3–3.6) for 25–29 years, 3.9 (95% CI 3.3–4.5) for 30–34 years, 6.8 (95% CI 5.9–7.9) for 35–39 years, and 11.2 (95% CI 8.8–14.3) for ≥ 40 years of age. Patients who were ≥ 40 years of age had a significantly higher mortality rate compared to that in other age groups. Hemorrhagic stroke was the most common cause of death in patients aged ≥ 40 years (15/65 [23%]), and preeclampsia (8/15 [54%]) was the most common cause of hemorrhagic stroke. Maternal mortality is significantly higher in older than in younger pregnant women in Japan, with hemorrhagic stroke being the most common cause of maternal death among women > 40 years of age. More than half of hemorrhagic strokes are associated with hypertension disorder of pregnancy. These facts should be considered by women who become pregnant at an advanced age and by healthcare providers involved in their perinatal care.